(untitled) - Ozawa, Ichiro (Tokyo, 1994)
Ozawa is one of the political leaders who masterminded the 1993 fall from power of Japan's Liberal Democratic Party, which had dominated the government since 1955. In this book, widely read in Japan, he spells out his ideas for a broadly based reform of Japanese political and social life, intended to revolutionize his country in the years ahead. Concentrating on three main areas (political reform, Japan's role in international affairs, and the reform of Japanese society), Ozawa argues for what amounts to revolutionary new directions in all three areas, ranging from the decentralizing of Japan's highly centralized political system, to a more active and dynamic Japanese role in international peacekeeping efforts, to the engendering of greater individualism and independent thinking among his country's citizenry. Both for Ozawa's provocative ideas and because of his influential status, this book is highly recommended for anyone interested in contemporary Japan.
Keywords: Political planning; Japan